The role of biochar properties in influencing the sorption and desorption of Pb(II), Cd(II) and As(III) in aqueous solution. (1st April 2017) - Zama, Eric F.; Zhu, Yong-Guan; Reid, Brian J.; Sun, Gou-Xin
Abstract: The chemical and physical properties of 20 biochars produced at 350, 450, 550 and 650 °C were investigated to determine the key roles they play in the sorption and desorption of three potentially toxic elements (Pb, Cd, As). Biochar surfaces were studied using scanning electron microscopy, Fourier transform infra-red spectroscopy, X-ray diffraction and X-ray photoelectron spectroscopy. Organic functional groups (e.g. COOH, CO, CX), inorganic minerals (CaCO3, SiO2, Ca2 Si5 O10 ·3H2 O) and cations (K +, Ca 2+, Mg 2+, Na + ) controlled PTE sorption significantly while physical properties (morphology, surface area) showed little influence on the sorption of potentially toxic elements. Four major mechanisms accounted for the exceptionally high Pb(II) sorption by all 20 biochars (97.5–99.8%) while Cd(II) and As(III) sorption (<90% and 42% respectively) were controlled by two mechanisms (precipitation and electrostatic attraction) only. Thermodynamic studies suggested that Pb and Cd sorption on a majority of biochars was spontaneous and endothermic while As sorption was also endothermic but not spontaneous. Sorbed PTEs were observed to be very stable over a wide range of pH values (3.5–9.5) with desorption ranging from 0.2 to 16.5%. Detailed understanding of how biochar surface properties interact with PTEs increases the possibility of developing cost effective and engineered biochars with exceptional sorption characteristics. Graphical abstract: Summary of major sorption processes and X-ray photoelectron spectroscopy (XPS) survey scan for mulberry wood biochar at 650 °C. Highlights: 20 biochars from 5 biomass materials were used for Pb, Cd and As sorption in solution. Chemical properties (functional groups, ions, minerals) controlled sorption significantly. The number of mechanisms in sorption processes determine biochar sorption capacity. The stability of sorbed contaminants on biochar (in soil or water) is pH-dependent. Understanding biochar properties enhances its engineering for superior sorption qualities.